A cladistic analysis of Gorytina (Hymenoptera: Crabronidae: Bembicini), with a reclassification of the subtribe - Nemkov, Pavel G.; Pulawski, Wojciech J. (Zootaxa, 2009)
Based on a cladistic analysis of the digger wasp subtribe Gorytina, the subtribes Argogorytina Nemkov and Lelej 1996, stat. resurr. (consisting of Argogorytes Ashmead 1899, Neogorytes Bohart in Bohart and Menke 1976, and Pterygorytes Bohart 1967), and Trichogorytina, subtrib. nov. (genus Trichogorytes Rohwer 1912 only) are removed from Gorytina. The genus Pterygorytes Bohart 1967 is transferred to Handlirschiina. New generic synonyms are: Pseudoplisus Ashmead 1899, and Leiogorytes Bohart 2000 = Gorytes Latreille 1805; and Malaygorytes Nemkov 1999 = Argogorytes Ashmead 1899. Thirteen species originally described in Pseudoplisus are transferred to Gorytes (new comb.): P. butleri Bohart 1969, P. californicus Bohart 1969, P. catalinae Bohart 1969, P. claripennis Bohart 1969, P. erugatus Bohart 1969, P. flavidulus Bohart 1969, P. hadrus Bohart 1969, P. imperialis Bohart 1969, P. nigricomus Bohart 1969, P. ocellatus Bohart 1969, P. samiatus Bohart 1969, P. willcoxi Ohl 2009, and P. tanythrix Bohart 1969. Also transferred to Gorytes (new comb.) are Leiogorytes guerrero Bohart 2000, Arpactus nyasicus R. Turner, 1915 and the following twelve species originally described in Gorytes but currently placed in Pseudoplisus: G. abdominalis Cresson 1865, G. aequalis Handlirsch 1888, G. divisus F. Smith 1856, G. effugiens Brauns 1911, G. fasciatus W. Fox 1896, G. montanus Cameron 1890, G. natalensis F. Smith 1856, G. ranosahae Arnold 1945, G. rubiginosus Handlirsch 1888, G. rufomaculatus W. Fox 1896, G. smithii Cresson 1880, and G. venustus Cresson 1865. Malaygorytes konishii (Nemkov 1999) is transferred to Argogorytes (new comb.). Updated diagnoses of Gorytes and Argogorytes are provided.